Concentrations of "legacy" and novel brominated flame retardants in matched samples of UK kitchen and living room/bedroom dust. (April 2016) - Kuang, Jiangmeng; Ma, Yuning; Harrad, Stuart
Abstract: Concentrations of polybrominated diphenyl ethers (PBDEs), hexabromocyclododecanes (HBCDDs) and 5 novel brominated flame retardants (NBFRs) were measured in paired samples of kitchen and living room/bedroom dust sampled in 2015 from 30 UK homes. BDE-209 was most abundant (22–170, 000 ng/g), followed by γ-HBCDD (1.7–21, 000 ng/g), α-HBCDD (5.2–4, 900 ng/g), β-HBCDD (2.3–1, 600 ng/g), BDE-99 (2.6–1, 440 ng/g), BDE-47 (0.4–940 ng/g), decabromodiphenyl ethane (DBDPE) (nd-680 ng/g) and bis(2-ethylhexyl)-3, 4, 5, 6-tetrabromo-phthalate (BEH-TEBP) (2.7–630 ng/g). The concentrations in kitchens and living rooms/bedrooms are moderate compared with previous studies. Concentrations of BDE-209 in living room/bedroom dust were significantly lower and those of DBDPE significantly higher (p < 0.05) compared to concentrations recorded in UK house dust in 2006 and 2007. This may reflect changes in UK usage of these BFRs. All target BFRs were present at higher concentrations in living rooms/bedrooms than kitchens. With the exception of BDE-28, pentabromoethylbenzene (PBEB) and DBDPE, these differences were significant (p < 0.05). No specific source was found that could account for the higher concentrations in living rooms/bedrooms. Graphical abstract: Highlights: First report of BFRs in domestic kitchen dust. Levels of most BFRs significantly lower in kitchen than living room/bedroom dust. Lower levels in kitchens may be due to more frequent cleaning and fewer BFR sources. BDE-209 and DBDPE in house dust respectively decreased and increased since 2006–07.